2004
DOI: 10.1103/physrevb.69.134114
|View full text |Cite
|
Sign up to set email alerts
|

Constrained shearing of a thin crystalline strip: Application of a continuum dislocation-based model

Abstract: The problem of simple shearing of a constrained thin crystalline strip posed by Shu et al. ͓J. Mech. Phys. Solids 49, 1361 ͑2001͔͒ is reanalyzed using a nonlocal continuum dislocation-based model of plastic deformation that accounts for the flexibility of curved dislocations carrying the plastic deformation. Attention is paid to the inhomogeneous profiles of plastic slip and lattice rotation as well as to the size-dependent material response of the strip in single slip and symmetric double slip. Additional bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…We note the boundary layer of the steeply changing orientation in the last loading step that has not been properly resolved. Already the earlier applications of the present model have shown that pronounced boundary layers characterized by steep gradients or even steps in plastic slip occur in the vicinity of impenetrable interfaces [22,23,25]. In accord with the above analysis, we observed upcoming spurious oscillations that we have suppressed by using extremely fine discretization of the space variable as well as extremely small time steps, which is computationally very expensive.…”
Section: Eulerian Evolution Equations In 1dsupporting
confidence: 70%
See 4 more Smart Citations
“…We note the boundary layer of the steeply changing orientation in the last loading step that has not been properly resolved. Already the earlier applications of the present model have shown that pronounced boundary layers characterized by steep gradients or even steps in plastic slip occur in the vicinity of impenetrable interfaces [22,23,25]. In accord with the above analysis, we observed upcoming spurious oscillations that we have suppressed by using extremely fine discretization of the space variable as well as extremely small time steps, which is computationally very expensive.…”
Section: Eulerian Evolution Equations In 1dsupporting
confidence: 70%
“…Unlike as in a local theory, the distribution and amount of plastic slip in the present model depends on the width H of the plastic channel, cf. Sedláček and Werner [25]. The results are shown in Fig.…”
Section: Eulerian Evolution Equations In 1dmentioning
confidence: 76%
See 3 more Smart Citations